Social dialog i Øst- og Centraleuropa - Mailand, Mikkel (Økonomi & Politik, 2026)
»For Western politicians and a great deal of fly-in academics and journalists, the reformed East seems to present a uniform picture. They arrive at modernised airports, stay at a 5-star hotel (the local Sheraton/Hilton/Marriott), converse with Western-trained young native professionals in a Western language, read the Prague Post, Budapest Sun, Warsaw Voice/Baltic Times for the US-perceived version of the local events, look at the macro-economic data, which are mostly good, stroll through the renovated inner cities of Tallinn, Vilnius, Prague and Budapest, be wined and dined in the best restaurants, and return with the impression that people are happy and more and more prosperous, that the transition worked equitably and effectively, and that a new tiger economy is well on its way. Accession to the European Union, then, appears to be unproblematic and enlargement negotiations and the adoption and implementation of EU legislation, including the social policy acquis, a pure technicality« (Rothacher 2000: 21).